Impact of impeller blade count on inlet flow pattern and energy characteristics in a mixed-flow pump - Zhu, Yadong; Jiao, Haifeng; Wang, Shihui; Lu, Zelin; Chen, Songshan (Frontiers in Energy Research, 2024)
Mixed-flow pumps, which amalgamate centrifugal and axial-flow attributes, play a pivotal role in various sectors due to their high efficiency and versatility. This paper, utilizing numerical simulation and experimental validation, addresses the critical role of impeller blade count in mixed-flow pump performance. It investigates the effect of the number of impeller blades on the energy dissipation mechanism and inlet flow pattern of a mixed-flow pump. The results reveal that dynamic and static interference effects, along with the separation vortex due to flow separation, are the main sources of energy dissipation in the pump. Under part-load and part-overload conditions, the increase in the number of blades contributes to the improvement of the flow pattern and performance but may induce more intense rotating stall effects under part-load conditions. In overload conditions, the increase in the number of blades significantly amplifies the volume of the inlet vortex structure, consequently deteriorating the inlet conditions of the impeller. This study provides valuable insights for the design and optimization of mixed-flow pumps.